DNA sequencing: the end of a near-monopoly - Jordan, Bertrand (M.S. Médecine sciences, 2025)
For the last decade, the field of DNA sequencing has been dominated by a single company, Illumina, with very limited competition. However, a new method with superior performance and lower cost has recently been announced by Roche, a major pharmaceutical and diagnostics company, and promises to have a large impact, especially (but not exclusively) for medical applications.